Toward a Grounded Theory: A Qualitative Study of Vision Statement Development - Kirkpatrick, Shelley A. (Journal of Management Policy and Practice, 2017)
Considerable research demonstrates the significant, positive impact of vision statements on organizational, team, and individual performance. However, little research exists on developing effective vision statements. Moving toward a grounded theory of vision statement development, 30 interviews were conducted with organizational leaders to identify and describe the approaches they used to develop their vision statements. Five categories of approaches were identified as a typology: 1) Uncommunicated, 2) Unstated yet Implemented, 3) Formally Stated, 4) Refined, and 5) Re-examined. Representative quotes from the leaders are presented to support and describe each category. Suggestions for future research, along with study limitations, are discussed.